Avaliação do processo de coagulação/floculação seguido por filtração na remoção de matéria orgânica natural - Santos, Tassia Rhuna Tonial dos (2014)
An important step in water treatment is disinfection. However, the chlorine used in this step may react with natural organic matter (NOM) in the water to form compounds called trihalomethane (THM) .THM are highly toxic, carcinogenic and mutagenic. Thus, this study aims to compare the efficiency of poly aluminum coagulants (PAC), Moringa oleifera Lam seeds without oil, Mo (et) , this extracted by ethanol, Moringa oleifera Lam seeds Lam without oil, Mo (hex) extracted with hexane and that associated with the anionic polymer PA0823, llo (hex + pol). The process comprises a step of coagulation/flocculation followed by filtration using a column containing activated charcoal from coconut palm. Assays were performed in Jar Test, using water from Pirapó river, Lm Maringá, Paraná with coagulant dosages of 9.5 mg L1 for PAC, 50 mg L 1 for Mo (et), 30 mg L1 for Mo (hex) and for Mo (hex + pol), was used the optimal dosage of Mo (hex) added 0.1 mg L1 of polymer. In sequence, the step of filtration column containing 150 g of activated charcoal coconut palm was realized. After each step, samples were collected to evaluate the removal efficiency of quality parameters: apparent color, turbidity, decreased concentration of dissolved organic carbon (DOC) and compounds with UV254nm absorption, as well as the minimizing of THM formation. lt was found that the treatment of coagulation/flocculation using natural coagulants followed by filtration through activated carbon were able to reduce the values of treated water physico-chemical parameters with reduced formation of total trinalometnanes (THl IT). When the anionic polymer was used as the auxiliary coagulation aid to lVlo evaluated parameters snowed the best removal of apparent color 97.98% Turbidity 97.43%, UV254nm 95.57% and COD 99.77%, and present a longer filter life and reduced settling time, snowing up to be a coagulant with potential possible uses in treatment plants in whole or in part for commercial coagulant PAC replacement.